Operação periódica de um leito gotejante de carvão ativado para redução da emissão do poluente atmosférico SO2 com geração de ácido sulfúrico - Pizzo, Sandro Megale (2003)
A laboratory-scale investigation of SO2 scrubbing was carried out in a 77.92mm (diameter) × 80.00mm trickle bed with 2.00-2.36mm activated carbon particles using continuous and periodically interrupted liquid flows. The effects of cycle period (10 and 20 minutes), cycle split (0.1, 0.2 and 0.3), superficial gas velocity (20, 40 and 60mm/s), and superficial liquid velocity (2mm/s) on SO2 removal and sulfuric acid production were investigated using a simulated flue gas containing SO2 at 500, 1,000 and 1,500ppm. The average removal efficiency of the periodic operation varied from 40 to almost 100%. The major variables controlling periodic operation performance were found to be the superficial gas velocity and the SO2 concentration. The extent of SO2 removal increased with decreasing cycle period and increasing split. Continuous operation runs achieved practically 100% scrubbing efficiency in all tests performed. Sulfuric acid production rates ranged from 0.649×10-8 to 0.256×10-7mol/g catalyst.s. The concentration of sulfuric acid produced was proportional to both the initial SO2 concentration and the gas superficial velocity. Some sulfuric acid production rates data for periodic operation overlapped those obtained in continuous liquid flow experiments. The advantage for the periodic operation was the higher acid concentrations produced and the lower pressure drops across the trickle bed without carbon losses. However, sulfuric acid production should not be regarded as an end in itself for the periodic operation, as the main goal of this gas treatment route is the removal of sulfur dioxide.